The a3Σ+ state of KCs revisited: Hyperfine structure analysis and potential refinement. (June 2022) - Krumins, V.; Tamanis, M.; Ferber, R.; Oleynichenko, A.V.; Skripnikov, L.V.; Zaitsevskii, A.; Pazyuk, E.A.; Stolyarov, A.V.; Pashov, A.
Highlights: High-resolution spectroscopy. Coupled channels deperturbation. Hyperfine structure. Relativistic ab initio calculations. Abstract: Laser-induced fluorescence spectra of the c 3 Σ + ( v c, J c = N c ) → a 3 Σ + ( v a, N a = J c ± 1 ) transitions excited from the ground X 1 Σ + state of 39 K 133 Cs molecule were recorded with Fourier-transform spectrometer IFS125-HR (Bruker) at the highest achievable spectral resolution of 0.0063  cm − 1 . Systematic study of the hyperfine structure (HFS) of the a 3 Σ + state for levels with v a ∈ [ 0, 27 ] and N a ∈ [ 24, 90 ] shows that the splitting monotonically increases with v a . The spectroscopic study was supported by ab initio calculations of the magnetic hyperfine interaction in X 1 Σ + and a 3 Σ + states. The discovered variation of the electronic matrix elements with the internuclear distance R is in a good agreement with the observed v a -dependencies of the HFS. Overall set of available experimental data on the a 3 Σ + state was used to improve the potential energy curve particularly near a bottom, providing the refined dissociation energy D e = 267.21 ( 1 )   cm − 1 . The ab initio HFS matrix elements, combined with the empirical X 1 Σ + and a 3 Σ + PECs in the framework of the invented coupled-channel deperturbation model, reproduce the experimental term values of both ground states within 0.003  cm − 1 accuracy up to their common dissociation limit.